Gut dysbiosis is associated with increased blood–brain barrier permeability and cognitive impairment in elderlies with coronary heart disease - Di, Lichao; Huang, Peiying; He, Yeju; Sun, Na; Chi, Liwei; Huang, Lining (Frontiers in Aging Neuroscience, 2025)
ObjectiveThe gut-brain axis is recognized as a critical pathway through which gut microbiota influences neurological health. However, the complex interplay between gut microbiota composition, blood–brain barrier (BBB) integrity, and cognitive function in elderly individuals with coronary heart disease (CHD) experiencing mild cognitive impairment (MCI) remains insufficiently elucidated. This study aimed to investigate these relationships in a cohort of 40 elderlies with CHD, comparing those with MCI to those with normal cognition (NC), focusing on microbial diversity, specific taxa alterations, BBB permeability, and their correlations with cognitive performance.MethodsThis preplanned secondary analysis utilized data from two prospective cohort studies, enrolling elderlies with CHD (≥60 years). Participants were categorized into NC (n = 20) and MCI (n = 20) groups based on standardized neuropsychological assessments. Fecal samples underwent 16S rRNA gene sequencing (V3-V4 region) to evaluate gut microbiota diversity and composition. BBB permeability was quantified using dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), specifically measuring the volume transfer constant (Ktrans) in the hippocampus.ResultsCompared to the NC group, MCI patients exhibited significantly reduced gut microbial α-diversity (Chao1 index: p = 0.002; Shannon index: p = 0.009) and distinct β-diversity profiles (Bray–Curtis dissimilarity, PERMANOVA, p = 0.003). LEfSe analysis identified depletion of key short-chain fatty acid (SCFA)-producing taxa in the MCI group, including at the family level (Ruminococcaceae, p = 0.016; Rikenellaceae, p = 0.042; and Barnesiellaceae, p = 0.038) and genus level (Faecalibacterium, p = 0.003 and Oscillospira, p = 0.002). Hippocampal BBB permeability (Ktrans) was significantly elevated in MCI patients (6.04 ± 3.02 vs. 3.90 ± 1.03 × 10−3 min−1, p = 0.006) and inversely correlated with the relative abundance of Faecalibacterium (Spearman’s r = −0.466, p = 0.002) and Oscillospira (Spearman’s r = −0.322, p = 0.043). Conversely, these genera showed positive correlations with Montreal Cognitive Assessment-Basic (MoCA-B) scores (Faecalibacterium: r = 0.596, p < 0.001; Oscillospira: r = 0.369, p = 0.019).ConclusionElderlies with CHD and MCI demonstrate significant gut dysbiosis, characterized by reduced microbial diversity and depletion of SCFA-producing taxa, notably butyrate producers. These microbial alterations are correlated with increased BBB permeability in the hippocampus and diminished cognitive function. These findings highlight the potential role of the gut-brain axis in the pathogenesis of cognitive decline in this vulnerable population and suggest that targeting gut microbiota could be a therapeutic avenue.